The social mentality theory of self-compassion and self-reassurance: The interactive effect of care-seeking and caregiving. Issue 5 (2nd September 2016) - Hermanto, Nicola; Zuroff, David Charles
ABSTRACT: The aim of this study was to test social mentality theory, which views self-compassion/reassurance as a form of intrapersonal relating in which the interpersonal mentalities of care-seeking and caregiving are activated. Self-report measures of motivations, cognitions, and behaviors related to seeking and receiving care from others were administered to 195 students. Self-compassion/reassurance was predicted by the interaction of care-seeking and caregiving, with the positive effect of care-seeking intensified at high caregiving. As hypothesized, the combination of high care-seeking and high caregiving predicted the highest level of self-compassion/reassurance. The lowest level of self-compassion/reassurance was predicted by the combination of low care-seeking and high caregiving consistent with the concept of compulsive caregiving. Findings suggest that fostering a kinder way of relating to oneself may be achieved through more effective care-seeking and caregiving with others.